Monitoring short-term labour cost developments in the European Union: which indicators to trust - Mourre, Gilles; Thiel, Michael; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper reviews the available indicators in the European Union to monitor short-term labour cost developments, i.e. of quarterly frequency, with a special focus on the euro area. It clarifies concepts, provides information on availability and compares the indicators against various statistical criteria, their historical track record and their predictive capacities. The paper mainly focuses on the supply side, particularly considering labour cost developments in terms of risks for price stability. It is found that no single indicator can be considered clearly superior and able to replace the others without loss of information, as each indicator concentrates on a specific dimension of labour costs and is affected by statistical flaws. The assessment of short-term wage developments should reasonably be based on the broadest available set of statistics so as to get a balanced and careful view. The empirical analysis shows that when forecasting core inflation one-step ahead for the euro area as a whole, the labour cost index and the ECFIN wage indicator display the higher predictive accuracy. Moreover, composite labour cost indicators (encompassing at least two indicators) clearly outperform any single wage indicator. Compensation per employee empirically appears the best, albeit weak, leading wage indicator of private consumption.
Economic Papers